Clinical Safety and Preliminary Efficacy of Plasmid pUDK-HGF Expressing Human Hepatocyte Growth Factor (HGF) in Patients with Critical Limb Ischemia. Issue 4 (October 2015) - Cui, S.; Guo, L.; Li, X.; Gu, Y.; Fu, J.; Dong, L.; Song, H.; Chen, X.; Lu, Y.; Hu, C.; Xiao, F.; Zhu, D.; et al.
Abstract : Objective: Critical limb ischemia (CLI) is the most severe form of peripheral arterial disease and a major unmet public health care need. This phase I clinical study was performed to assess the safety and preliminary efficacy of naked plasmid DNA (pUDK-HGF) expressing human hepatocyte growth factor (HGF) in patients with critical limb ischemia (CLI). Design: Twenty-one patients with CLI were enrolled and randomly divided into four dose groups (4–16 mg) to receive local injection of pUDK-HGF into ischemic calf and/or thigh muscles twice on days 1 and 15. Safety, including adverse events and physiological parameters, and preliminary efficacy, including pain severity score (VAS), ulcer size, transcutaneous oxygen pressure (TcPO2 ), and ankle brachial index (ABI), were evaluated throughout a 3 month follow up period. Results: All doses of pUDK-HGF were well tolerated by the patients. None of the adverse effects was considered to be related to pUDK-HGF injection. Two significant clinical results were observed after pUDK-HGF administration. The mean VAS value of all patients decreased from 4.52 at baseline to 0.30 ( p < .01), and pain had disappeared in 14 out of 17 evaluable patients by day 91. Two of four ulcers had completely healed, with the other two patients having more than 25% ulcer size reduction in the long axis diameter. Of five patients with gangrene, one gangrenous wound had healed completely and two patients showed marked size reduction by day 91. The mean hemodynamic parameters (ABI, TcPO2 ) were also improved. Conclusion: Intramuscular injection of pUDK-HGF is safe, and may provide symptomatic relief for CLI patients. A larger, randomized, double blinded phase II trial will provide more information on safety and efficacy.